2016
DOI: 10.1074/jbc.m116.737395
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Mutant Mucor hiemalis Endoglycosidase That Acts on Core-fucosylated N-Glycans

Abstract: Endo-␤-N-acetylglucosaminidase M (Endo-M), an endoglycosidase from the fungus Mucor hiemalis, is a useful tool for chemoenzymatic synthesis of glycoconjugates, including glycoprotein-based therapeutics having a precisely defined glycoform, by virtue of its transglycosylation activity. Although Endo-M has been known to act on various N-glycans, it does not act on core-fucosylated N-glycans, which exist widely in mammalian glycoproteins, thus limiting its application. Therefore, we performed site-directed mutage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 55 publications
0
8
1
Order By: Relevance
“…Unexpectedly, the Endo-M N175Q mutant, without the help of Endo-S, showed approximately 5% transglycosylation efficiency towards core-fucosylated IgG ( Fig 4A ). This may be in conflict with a previous report by Katoh et al They reported that the Endo-M N175Q mutant scarcely transglycosylated SG-oxazoline to the core-fucosylated acceptor at a donor-to-acceptor ratio of 1:1, whereas their engineered Endo-M N175Q/W251 double mutant showed approximately 5% transglycosylation efficiency [ 32 ]. The apparent conflict may be related to differences in conditions such as the type of donor glycan and its ratio to acceptor.…”
Section: Discussioncontrasting
confidence: 74%
“…Unexpectedly, the Endo-M N175Q mutant, without the help of Endo-S, showed approximately 5% transglycosylation efficiency towards core-fucosylated IgG ( Fig 4A ). This may be in conflict with a previous report by Katoh et al They reported that the Endo-M N175Q mutant scarcely transglycosylated SG-oxazoline to the core-fucosylated acceptor at a donor-to-acceptor ratio of 1:1, whereas their engineered Endo-M N175Q/W251 double mutant showed approximately 5% transglycosylation efficiency [ 32 ]. The apparent conflict may be related to differences in conditions such as the type of donor glycan and its ratio to acceptor.…”
Section: Discussioncontrasting
confidence: 74%
“…In summary, ENGases identified in this report could be useful as tools not only for analyzing the oligosaccharide contents of antibodies (basic research), but they could also be useful as tools for developing therapeutic antibody pharmaceuticals (biomedical application), such as an immunomodulatory therapeutic agent for the treatment of autoimmune disorders. In a recent study, it was reported that W251N mutant of Endo-M can catalyze the hydrolysis of fucosylated N -glycans, a feature is not seen in wild-type Endo-M 41 . At present, we do not know which amino acid residues in Endo-SBs are specifically involved in recognizing fucosylated oligosaccharides, because Endo-SBs belong to the GH18 family, whereas the Endo-M belongs to the GH85 family.…”
Section: Discussionmentioning
confidence: 99%
“…This β ‐mannosylation via anomeric O ‐alkylation was next utilized in the synthesis of the hexasaccharide core of complex fucosylated N ‐linked glycans . For instance, bi‐antennary α ‐(2,3)‐sialylated core‐fucosylated N ‐glycan dodecasaccharide was found on alpha fetoprotein (AFP) isolated from patients with hepatocellular carcinoma.…”
Section: Resultsmentioning
confidence: 99%